PEMBERIAN KOTORAN LARVA KUMBANG TANDUK (Oryctes rhinoceros) UNTUK MENINGKATKAN PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PEMBIBITAN UTAMA - Desi Rahmiaty Pulungan; - Wardati; Hafiz Fauzana (Sistem Informasi, 2018)
Feces of rhinoceros beetles larvae (kolarhino) is an organic fertilizer that is obtained from defecation of rhinoceros beetles larvae that using empty palm fruit bunches as the feed. This research aims to look at the effect of giving kolarhino and get the best dose for the growth of oil palm seedlings (Elaeis guineensis Jacq) in the main nursery. The researched was carried out at Faculty of Agricultural experiment station, University of Riau from August to November 2016. This research using a completely randomized design which consist of 6 treatments and 4 replications level: 0, 25, 50, 75, 100 and 125 g/plant. Giving kolarhino on oil palm seedlings showed a significant in the increase of number of leaves, the increase of diameter stump, root volume and dry weight of seedlings but showed not significant to plant height increment and shoot root ratio. Giving kolarhino at a dose of 75 g/plant up to 125 g/plant increase of number of leaves, the increase of diameter stump and root volume, while the dose of 100 g/plant and 125 g/plant increase of dry weight of oil palm seedlings.